Reduced Arterial Stiffness and Ankle Blood Pressure Following Stretching Exercise in Postmenopausal Women - Boonpim, Hataichanok; Wanpen, Sawitri; Chanavirut, Raoyrin; Apaijit, Kwanjit; Kukongviriyapan, Upa; Nakmareong, Saowanee (Journal of Physiological and Biomedical Sciences, 2017)
An association between muscle flexibility and arterial elasticity has previously reported. Therefore, this study aimed to investigate the effects of 6-week stretching training on arterial stiffness in postmenopausal women. Forty postmenopausal women (mean age 55.00 + 3.70 years) were randomly allocated to control group (n = 20) or stretching group (n = 20). Six weeks of stretching exercise was done in major muscle groups (neck, trunk, upper and lower extremities) for 30 minutes a day, 5 days a week. Arterial stiffness was assessed by brachial-ankle pulse wave velocity (baPWV). In addition, ankle blood pressure was measured pre and posttraining. After 6 weeks, baPWV significantly improved in the stretching group (P < 0.05). Moreover, ankle systolic blood pressure significantly decreased in the training group compared with control participants (P < 0.05). A positive and significant correlation between ankle systolic blood pressure and baPWV was found (r = 0.454, P = 0.003). This study shows that stretching training was effective to reduce arterial stiffness and ankle blood pressure in postmenopausal women. Overall findings provided the therapeutic efficacy of stretching exercise improve arterial elasticity and blood pressure in postmenopausal women.